Benefits of Virtual Reality in Medical and Healthcare Training - Altalhi, Suad Hamadi; Hamed, Baraa Mohammed; Alnasser, Badriah Mohammed; Alqahtani, Waad Saleh; Alzaidi, Shatha Magboul; Asiri, Fatimah Hassan (Journal of Posthumanism, 2024)
Recently, virtual reality “VR” has emerged as promising training method for healthcare providers. VR is a simulation event done by the combination of computer-generated software and physical hand devices. It is able to provide an immersive and interactive environment for its users. VR has been introduced in medical and nursing training programs since it offers a highly interactive and realistic learning environment, exceeding the traditional methods. However, the benefits of VR over traditional training methods in medical and healthcare training are still debatable as shown by current evidence. The aim of this review is to explore current evidence discussing the benefits of VR in medical and healthcare training. VR has shown positive outcomes in various medical fields training from the providers’ perspective, including emergency medicine training, radiology training, and disaster medicine. It also has shown positive outcomes from patients’ perspective, including stress and anxiety relieving training and gait and balance training. However, confirming VR superiority over traditional methods still needs further research. Additionally, VR was associated with nausea, vomiting, and headache which known as “cybersickness”.